The Anticancer Effects of Atractylenolide III Associate With the Downregulation of Jak3/Stat3-Dependent IDO Expression - Liu, Jun-bao; Chen, Dan; Bao, Ting-ting; Fan, Fang-tian; Yu, Chen (Frontiers in Pharmacology, 2020)
Background: Indoleamin-2, 3-dioxygenase-1(IDO), has been identified as a checkpoint protein involved in generating the immunosuppressive tumor microenvironment that supports tumor growth. It has been reported that atractylenolide III (ATLIII) has anticancer and immune modulatory effects. This study is to determine the anticancer effects of ATLIII with the Jak3/Stat3-dependent IDO inactivation. Methods: We assessed the cytotoxicity of ATLIII and IFN-γ on lung cancer cells by MTT. We determined the efficacy of ATLIII on IFN-γ induced IDO expression by RT-PCR and Western blot. We also determined the efficacy of ATLIII on Jak3/Stat3 pathway expression induced by IFN-γ, and Jak3/Stat3 dependent IDO activation. Further molecular docking assay predicted the binding activity and site of ATLIII to Jak3 protein. Additional immunofluorescence staining was used to measure the Stat3 intracellular localization. Finally, we performed mouse animal experiments to observe changes in the expression of IDO, p-Jak3, p-Stat3 and tryptophan/kynurenine after ATLIII administration. Results: ATLIII showed no cytotoxicity at wide of dosage range. ATLIII reduced the phosphorylation level of Jak3 and Stat3 in response to IFN-γ stimulation, then remarkably reduced the nuclear translocation of p-Stat3 by IFN-γ. At last ATLIII significantly down-regulated the expression level of IDO at a wide dosage range. Molecular docking assay showed that the oxygen atom on the five-membered ring of ATLIII was capable of forming a hydrogen bond with leu905-NH2 site of Jak3 protein. Further evidence showed that though IFN-γ had normal capacity to trigger Stat3 phosphorylation, nuclear translocation and promoter luciferase activity, however ATLIII failed to have to trigger efficacy on reducing these changes under forced Jak3-leu905 mutant expression condition. Finally, we confirmed this view in vivo experiments. Conclusions: ATLIII has shown significant efficacy to inhibit IFN-γ triggered Jak3/Stat3 pathway dependent IDO activation, and do so through a direct binding to Jak3 protein. This study elucidated a new mechanism for the anticancer effect of ATLIII, which may provide a feasible target for the clinical immunotherapy of malignant tumors.